Under the persimmon tree - Staples, Suzanne Fisher (New York : Square Fish, 2005)
During the 2001 Afghan War, the lives of Najmal, a young refugee from Kunduz, Afghanistan, and Nusrat, an American-Muslim teacher who is awaiting her huband's return from Mazar-i-Sharif, intersect at a school in Peshawar, Pakistan.
Keywords: Afghan War, 2001- -- Juvenile fiction; Afghanistan -- Juvenile fiction. -- History 2001